Study of Perceived Constraints Faced By Women Self Help Group Entrepreneurs - Manveer Singh , Basavaprabhu Jirli and Ashok Rai, (Indian Journal of Extension Education, 2014)
The study was conducted in Hathras (now Mahamaya Nagar) district of Uttar Pradesh state (India) in the year 2009-2010.Three blocks viz. Sasni, Hathras and Sikandrarao, consisted the study area. The sample size of the study was 250 self helpgroup members drawn from 50 SHG s by proportionate random sampling technique. The data were collected with the helpof a structured interview schedule. From the analysis of constraints, it was concluded that the unfavorable attitude of bankofficials¸ dependence on intermediaries and fluctuation of market price were the most serious constraints perceived by themembers of SHGs